Measurement of the cross-section for the process γ*γ* + hadrons at LEP - Dova, María Teresa (1999)
Measurements of the two-photon interaction e+e- → e+e- + hadrons at √s = 91 GeV and √s = 183 GeV are presented. The double-tag events, collected with the L3 detector. correspond to integrated luminosities of 140 pb-1 at 91 GeV and 52 pb-1 at 183 GeV. The cross-section of γ*γ* collisions has been measured at (Q2) = 3.5 GeV2 and (Q2) = 14 GeV2. The data agree well with predictions based on perturbative QCD, while the Quark Parton Model alone is insufficient to describe the data.